Real Estate and Consumption Growth as Common Risk Factors in Asset Pricing Models. (31st May 2016) - Carmichael, Benoît; Coën, Alain
Abstract: Using a linear multifactor pricing model, we study the influence of equity market, the consumption growth and the return on real estate wealth on asset returns. The real estate risk factor is proxied alternatively by the National Association of Real Estate Investment Trusts (NAREIT) index, unlevered NAREIT index and National Council of Real Estate Investment Fiduciaries property index. Estimates are based on CRSP's monthly decile portfolio returns from January 1972 to December 2013 (including the Vintage REIT era and the New REIT era). Generalized method of moment results show that the real estate factor is particularly useful to explain the cross‐sectional variation of returns in the last two decades generally associated with the so‐called real estate bubble .